Description of Fiscal Legislation and Changes in Years in Albania - Xhango, Edvin (European Journal of Economics and Business Studies, 2016)
The development of the appropriate tax law was very important but also very difficult for countries coming from a centrally planned economy. In this paper, the author discusses the framework of tax law drafted from 1993 until 2014. In the study we present as the legislation has changed in these years and have influenced legal solutions to improve business data; thus affecting the development of the economy. We have identified legal definitions that provide the right solutions for business as well as for the economy of the state. We have selected the popular items and the articles that encourage business to develop informal economy. For this study is the ratio of Value Added Tax and Income tax on gross domestic product, which from 1998 until 2014 is almost the same. Noting that Albania is the country with the size of informal economy 34-47 percent, the result is about the legal framework of deficiencies. Given the above results, we have studying business interests to develop the informal economy. For this aid comes in the study of Busato and Chiarini, 2004, by which it can be determined the cost of product development business to the informal economy. Calculations showed that the cost of the development of the informal sector is much lower than the fiscal burden. Based on the results we conclude that the legal framework needed to improved in terms of avoidance of tax evasion opportunities as recognition of all invoiced costs, increasing penalties for not declaring the income and improve the work of the tax administration.